Pengaruh Green Banking Disclosure dan Social Banking terhadap Nilai Perusahaan dengan Banking Sustainable Performance sebagai Variabel Mediasi - Alisa Qurrota A'yun Khoirul Bariyah; Marhaendra Kusuma; Rike Selviasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the effect of green banking disclosure and social banking on firm value with banking sustainable performance as a mediating variable. The population in this research consists of banking subsector companies listed on the Indonesia Stock Exchange during the 2021–2023 period, totaling 47 companies. The sampling technique used in this study was purposive sampling, resulting in a total of 30 data points that met the research criteria and could be analyzed. The analytical method employed was path analysis using SPSS version 25 to test the relationships among variables and the mediation effect. The results of this study indicate that green banking disclosure has a positive and significant effect on firm value. Social banking also has a positive and significant effect on firm value. Banking sustainable performance has a positive and significant effect on firm value as well. However, green banking disclosure does not have a positive and significant effect on banking sustainable performance, while social banking does have a positive and significant effect on banking sustainable performance. The mediation test results using path analysis reveal that banking sustainable performance is unable to mediate the effect of green banking disclosure on firm value. Conversely, banking sustainable performance successfully mediates the effect of social banking on firm value. These findings suggest that social banking is more effective in enhancing banking sustainable performance and firm value compared to green banking disclosure.